In Situ Growth of CoP Nanosheet Arrays on Carbon Cloth as Binder‐Free Electrode for High‐Performance Flexible Lithium‐Ion Batteries. Issue 51 (2nd November 2022) - Yang, Yang; Xia, Jun; Guan, Xianggang; Wei, Ziwei; Yu, Jiayu; Zhang, Shichao; Xing, Yalan; Yang, Puheng
Abstract: Cobalt phosphide (CoP) is considered as one of the most promising candidates for anode in lithium‐ion batteries (LIBs) owing to its low‐cost, abundant availability, and high theoretical capacity. However, problems of low conductivity, heavy aggregation, and volume change of CoP, hinder its practical applicability. In this study, a binder‐free electrode is successfully prepared by growing CoP nanosheets arrays directly on a carbon cloth (CC) via a facile one‐step electrodeposition followed by an in situ phosphorization strategy. The CoP@CC anode exhibits good interfacial bonding between the CoP and CC, which can improve the conductivity of the integrated electrode. More importantly, the 3D network structure composed of CoP nanosheets and CC provides sufficient space to alleviate the volume expansion of CoP and shorten the electron/ion transport paths. Moreover, the support of CC effectively prevents the agglomeration of CoP. Based on these advantages, when CoP@CC is paired with the NCM523 cathode, the full cell delivers a high discharge capacity 919.6 mAh g −1 (2.1 mAh cm −2 ) after 200 cycles at 0.5 A g −1 . The feasibility and safety of producing pouch cells are also explored, which show good flexibility and safety despite rigorous strikes (mechanical damage and severe deformations), implying a great potential for practical applications. Abstract : A binder‐free electrode is constructed by in situ growing cobalt phosphide (CoP) nanosheets arrays directly on a flexible carbon cloth (CC). This strategy effectively avoids the aggregation of CoP, enhances the transport efficiency of electrons/ions, and accommodates volume expansion of CoP nanosheets. Therefore, the CoP@CC anode exhibits enhanced electrochemical performance and good flexibility.